Glacier-related landforms and glacial lakes in Huascarán National Park, Peru - Vilímek, Vít; Klimeš, Jan; Červená, Lucie (Journal of maps, 2016)
The map of lakes and selected glacier-related landforms in Huascarán National Park was created describing their spatial distribution and selected properties related to their development. This work presents additional information on previous lake inventories that was not available prior to its completion despite the fact that some of the newly collected information is important for glacial lake flood hazard assessment. The ongoing environmental changes documented in the national park are affecting the number, size, spatial distribution and development of the glacial lakes. Many of the lakes are also filled with sediment, as well as subject to outburst floods. The lake typology is based on the character of their dam, whilst moraine ridge types are defined with specific geomorphological features that affect their stability. Over 1250 moraine ridges (longer than 200 m) were mapped and classified along with 2370 lakes each with a specific dam type. This represents the most detailed inventory which can be used for future statistical analysis or hazard assessment.